2023
DOI: 10.1124/pharmrev.122.000674
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pain Perception by Microbiota in Parkinson Disease

Zulmary Manjarres,
Margarita Calvo,
Rodrigo Pacheco

Abstract: Pain perception involves current stimulation in peripheral nociceptive nerves and the subsequent stimulation of postsynaptic excitatory neurons in the spinal cord.Importantly, in chronic pain, the neural activity of both peripheral nociceptors and postsynaptic neurons in the central nervous system is influenced by several inflammatory mediators produced by the immune system. Growing evidence has indicated that the commensal microbiota plays an active role in regulating pain perception by either acting directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 345 publications
(371 reference statements)
0
4
0
Order By: Relevance
“…SCFAs that reach the bloodstream might promote CNS homeostasis by reinforcing blood-brain barrier (BBB) integrity, avoiding neuroinflammation, affecting levels of neurotrophic factors, promoting serotonin biosynthesis, or directly activating the vagal afferent. Of note, in addition to diet and dysbiosis, the plasma concentration of SCFAs might be affected by the renin-angiotensin system [11], and by the energy requirements and lipids metabolism [12]. In this regard, acetate and butyrate might be converted into acetyl coenzyme A and subsequently used as substrate in the tricarboxylic acid cycle or beta-oxidation, while propionate might act as a precursor for gluconeogenesis in the liver [12].…”
Section: Neurological Pathologies Involving Imbalance Of Scfa Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs that reach the bloodstream might promote CNS homeostasis by reinforcing blood-brain barrier (BBB) integrity, avoiding neuroinflammation, affecting levels of neurotrophic factors, promoting serotonin biosynthesis, or directly activating the vagal afferent. Of note, in addition to diet and dysbiosis, the plasma concentration of SCFAs might be affected by the renin-angiotensin system [11], and by the energy requirements and lipids metabolism [12]. In this regard, acetate and butyrate might be converted into acetyl coenzyme A and subsequently used as substrate in the tricarboxylic acid cycle or beta-oxidation, while propionate might act as a precursor for gluconeogenesis in the liver [12].…”
Section: Neurological Pathologies Involving Imbalance Of Scfa Levelsmentioning
confidence: 99%
“…Of note, in addition to diet and dysbiosis, the plasma concentration of SCFAs might be affected by the renin-angiotensin system [11], and by the energy requirements and lipids metabolism [12]. In this regard, acetate and butyrate might be converted into acetyl coenzyme A and subsequently used as substrate in the tricarboxylic acid cycle or beta-oxidation, while propionate might act as a precursor for gluconeogenesis in the liver [12]. According to the crucial role of SCFAs in CNS homeostasis, altered levels of these metabolites have been associated with many neurological diseases.…”
Section: Neurological Pathologies Involving Imbalance Of Scfa Levelsmentioning
confidence: 99%
“…136−139 In another study, through quantitative RT-PCR analyses of fecal samples from 20 PD patients and 20 healthy persons, it was found that Desulfovibrio bacteria were hosted in the intestinal microbiota of all PD patients, with these bacteria being more abundant in PD patients than in healthy controls. 140 Apart from producing H 2 S, Desulfovibrio bacteria are recognized for their production of magnetite (some strains) and lipopolysaccharide, all these are probable elements adding to the clustering and accumulation of the α-syn protein. 98 5.4. α-Syn Pathology in PD and Its Association with Gut Dysbiosis.…”
Section: Intestinal Rise Of the Rare Phylum Thermodesulfobacteriotamentioning
confidence: 99%
“…The presence of Desulfovibrio bacteria links with the seriousness of PD. , Consequently, PD patients may experience excess H 2 S. While H 2 S can be beneficial in small quantities, acting as a gaseous neurotransmitter that regulates various body functions, including those in the GI, neuronal, respiratory, cardiovascular, renal, hepatic, and endocrine systems, elevated H 2 S levels resulting from a bloom in sulfate-reducing bacteria can become harmful . Such elevated H 2 S levels are associated with GI disorders such as ulcerative colitis, irritable bowel syndrome, and Crohn’s disease, all of which are linked to an increased risk of PD. In another study, through quantitative RT-PCR analyses of fecal samples from 20 PD patients and 20 healthy persons, it was found that Desulfovibrio bacteria were hosted in the intestinal microbiota of all PD patients, with these bacteria being more abundant in PD patients than in healthy controls . Apart from producing H 2 S, Desulfovibrio bacteria are recognized for their production of magnetite (some strains) and lipopolysaccharide, all these are probable elements adding to the clustering and accumulation of the α-syn protein …”
Section: Gut Dysbiosis In Pdmentioning
confidence: 99%